Anatomy of terror : from the death of bin Laden to the rise of the Islamic State - Soufan, Ali H. (W. W. Norton & Company, 2017)
"A compelling, definitive account of how and why bin Laden's ideology keeps rising from the dead. In early 2011, the heart of the Muslim world roiled in protest, consumed with the upheaval of the Arab Spring, The governments of Tunisia and Egypt had already fallen; those of Libya and Yemen would soon follow. Watching the chaos from his hideout in Pakistan, Osama bin Laden saw a historic opportunity: 'the next stage,' he declared, 'will be the reinstating of the rule of the caliphate.' Within weeks, bin Laden was dead, shot in the dark by a U.S. Navy SEAL. Commentators around the world began to prophesy al-Qaeda's imminent demise. But six years later, the reality is the reverse. The group's affiliates have swollen, and the Islamic State--al-Qaeda's most brutal spinoff to date--proclaims itself the reborn caliphate bin Laden foretold in his final weeks. In Anatomy of Terror, former FBI special agent and ... best-selling author Ali Soufan dissects bin Laden's brand of jihadi terrorism and its major offshoots, revealing how these organizations were formed, how they operate, their strengths, and--crucially--their weaknesses. This riveting account examines the new Islamic radicalism through the eyes of its flag-bearers, including a Jordanian former drug dealer whose cruelties shocked even his fellow militants, an Air Force colonel who once served Saddam Hussein, and a provincial bookworm who declared himself caliph of all Muslims. We meet Ayman al-Zawahiri, titular head of al-Qaeda; Saif al-Adel, an Egyptian ex-soldier who faked his own death to become the group's security chief; and bin Laden's own beloved son Hamza, a prime candidate to lead the organization his late father founded. To eliminate the scourge of terrorism, we must first know who the enemy actually is, and what his motivations are. Anatomy of Terror lays bare the psychology and inner workings of al-Qaeda, the Islamic State, and their spawn, and shows how the spread of terror can be stopped."--Jacket.